Effects of Job Accomplishment and Job Satisfaction in Work Performance of Non-teaching Staff in Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of the study is to determine Job Accomplishment and Job Satisfaction in theWork Performance of Non-Teaching Staff at Bestlink College of the Philippines. Job inAccomplishment had an average of 4.66, and the higher composite mean was 4.71. Thecomposite mean for the workplace is lower, 4.62. While the respondents overwhelminglysupported the overall mean of 4.05 for Job Satisfaction safety, they received the highestcomposite mean of 4.16. The lowest composite mean for belongingness statements is 3.88.Out of fifty respondents at the time of the study, non-teaching staff at Bestlink College of thePhilippines were selected as a sample.As a result, the institution has greatly benefited from the staff's excellent work ethic, goodcommunication, and regular attendance at work in terms of both job performance and highoutput.In order to encourage effective job performance, it is advised that universities and other post-secondary institutions should handle the issue of staff work attitude seriously.
Keywords: Psychology